Research faculty, entrepreneurship and commercialization: the case of Kansas State University - Metla, Chandra Mohan Reddy (Kansas State University, 2007)
Interest in commercialization of university research has accelerated since the Bayh-Dole Act (1980) granted authority to universities and federally-funded nonprofit institutions, among others, to obtain patents, grant licenses, and transfer custody of patents with the explicit purpose of promoting the utilization and marketing of their inventions. This interest is supported by these institutions' need to expand their funding sources as growth in their traditional funding has lagged their needs. This study seeks to assess the level of understanding of research commercialization and entrepreneurship aspects by the faculty researchers nearly 10 years after Bayh-Dole Act using a survey of university faculty. The results show that there is indeed the desire to move research from universities to the marketplace through technology commercialization and entrepreneurship, but there is need for educational programs to enhance the current perceptions about the commercialization and entrepreneurship among faculty. We show that this need is independent of the demographic characteristics of faculty but influenced the university's policies covering intellectual property and commercialization.
Keywords: Academic Entrepreneurship; Commercialization; Research Faculty; Economics, Agricultural (0503)